Nerve electrical stimulation treatment of xerostomia - XU Kehui; CHEN Li; DIAO Xiaoou; TIAN Min; WEI Jiao; NIU Lina; JIAO Kai (口腔疾病防治, 2022)
Patients with impaired quality of life associated with xerostomia need long-term treatment, and a nerve stimulator has the advantage of providing natural saliva and long-term management for patients with xerostomia by electrically stimulating the relevant secretory nerves to promote saliva production. A number of clinical trials have preliminarily demonstrated the efficacy of nerve electrical stimulation in the treatment of xerostomia. However, electrical stimulation has not yet become the mainstream treatment for xerostomia. Large prospective randomized controlled clinical trials are still needed to confirm its long-term effectiveness and safety. In addition, the design of nerve stimulators is of great significance for clinical application. The large volume and inconvenient treatment associated with the extra oral nerve stimulator and the first generation intraoral nerve stimulator hinder their clinical application and popularization. The second- and third-generation intraoral nerve stimulator devices are small, convenient to use and have great application prospects. Research on electrical nerve stimulators for xerostomia treatment is mainly concentrated in European and American countries, while there is very little domestic research. It is urgent to master the core technology for the research and development of electrical nerve stimulators. The innovation of miniaturization, efficient power supply, data feedback and packaging will be the key issues of electrical nerve stimulators in the future. In this paper, the treatment and research of electrical nerve stimulation for xerostomia are reviewed to provide a reference for related basic research and the clinical application of electrical stimulators treating xerostomia in China.